2011
DOI: 10.1111/j.1542-2011.2011.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function and Quality of Life for Women with Mild‐to‐Moderate Stress Urinary Incontinence

Abstract: Women with mild-to-moderate stress urinary incontinence, without or with lower stages of pelvic organ prolapse, demonstrated good sexual function, which correlated with physical and psychosocial factors. Health professionals need to perform multifaceted intake assessments on women with urinary leakage to customize their health promotion regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 33 publications
1
17
1
4
Order By: Relevance
“…This agrees well with research showing that women with pelvic floor disorders were as likely to be sexually active as women without pelvic floor disorders [51]. It is also in line with a study demonstrating that women with stress urinary incontinence, with or without POP, had good sexual function [52].…”
Section: Discussionsupporting
confidence: 91%
“…This agrees well with research showing that women with pelvic floor disorders were as likely to be sexually active as women without pelvic floor disorders [51]. It is also in line with a study demonstrating that women with stress urinary incontinence, with or without POP, had good sexual function [52].…”
Section: Discussionsupporting
confidence: 91%
“…UI has an adverse effect on the quality of life and sexual functions. However, the duration and severity of UI may not be correlated with the adverse effects on sexual functions 20,21 . Coital incontinence is directly associated with sexual dysfunction 22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the duration and severity of UI may not be correlated with the adverse effects on sexual functions. 20,21 Coital incontinence is directly associated with sexual dysfunction. 22 In this study, improvement in sexual functions has been observed in women after treatment of UI, which is in agreement with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…, Liebergall‐Wischnitzer et al . ). Women felt less feminine, less sexually attractive and also suffered poor body image (Coyne et al .…”
Section: Introductionmentioning
confidence: 97%
“…Sexuality is a fundamental aspect of well-being and can have a significant impact on women's health. UI has been demonstrated to have a negative impact on a woman's sexuality due to leakage which can lead to a decrease in quality of life, sexual activity and enjoyment while negatively affecting relationships (Achtari & Dwyer 2005, Lukacz et al 2007, Liebergall-Wischnitzer et al 2011. Women felt less feminine, less sexually attractive and also suffered poor body image (Coyne et al 2007, Zielinski et al 2009, Ratner et al 2011).…”
Section: Introductionmentioning
confidence: 99%